2017
DOI: 10.1090/mcom/3224
|View full text |Cite
|
Sign up to set email alerts
|

Dimension of mixed splines on polytopal cells

Abstract: The dimension of planar splines on polygonal subdivisions of degree at most d is known to be a degree two polynomial for d 0. For planar C r splines on triangulations this formula is due to Alfeld and Schumaker; the formulas for planar splines with varying smoothness conditions across edges on convex polygonal subdvisions are due to Geramita, McDonald, and Schenck. In this paper we give a bound on how large d must be for the known polynomial formulas to give the correct dimension of the spline space. Bounds ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Put J 1 = x r+1 , y r+1 : (x + y) r+1 ; I 1 can be obtained from J 1 by the change of coordinates x → x , y → −x + y . In [13,Lemma 7.18] it is shown that the initial ideal in(J 1 ) with respect to lexicographic order consists of the dim(J 1 ) d lexicographically largest monomials in the variables x and y. In other words, in(J 1 ) in lexicographic order is a so-called lex segment ideal (see [24,Chapter 2]).…”
Section: Theorem 53 (Steinitz)mentioning
confidence: 99%
See 1 more Smart Citation
“…Put J 1 = x r+1 , y r+1 : (x + y) r+1 ; I 1 can be obtained from J 1 by the change of coordinates x → x , y → −x + y . In [13,Lemma 7.18] it is shown that the initial ideal in(J 1 ) with respect to lexicographic order consists of the dim(J 1 ) d lexicographically largest monomials in the variables x and y. In other words, in(J 1 ) in lexicographic order is a so-called lex segment ideal (see [24,Chapter 2]).…”
Section: Theorem 53 (Steinitz)mentioning
confidence: 99%
“…It turns out that I 1 is a complete intersection generated in degrees (r + 1)/2 , (r + 1)/2 . This implies that the Hilbert function of I 1 has the following form (for a proof see [13,Corollary 7.17]):…”
Section: Theorem 53 (Steinitz)mentioning
confidence: 99%
“…for quite small m relative to r and it is possible to obtain quite accurate estimates for the smallest such m. However, this equation typically holds in degree far lower than dimension formulas are actually known (see [7]), so we focus on giving some coarse estimates that are easy to derive. Proposition 4.14.…”
Section: Polygonal Meshesmentioning
confidence: 99%
“…Computing the dimension of spline spaces is a highly non-trivial task in general for splines in more than one variable. Initiated by Strang [19,20], this is by now a classical topic in approximation theory and has been studied in a wide range of planar settings; e.g., on triangulations, polygonal meshes, and T-meshes [18,2,4,17,16,11,7,21,12,22]. Nonpolynomial spline spaces have also been studied in the same vein; e.g., [5].…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise we call the vertex star an open vertex star. In Equations 15 and 16 of [1], Alfeld, Neamtu, and Schumaker define functions (in terms of simple geometric and combinatorial data of ∆) which we denote by LB (∆, d, r) (11) and LB (∆, d, r) (12), respectively. In [1,Theorem 3], it is shown that dim H r d (∆) = LB (∆, d, r) for d ≥ 3r + 2 if ∆ is a closed vertex star and that dim H r d (∆) = LB (∆, d, r) for d ≥ 3r + 2 if ∆ is an open vertex star.…”
Section: Introductionmentioning
confidence: 99%